CLINICAL PATHOPHYSIOLOGY OF CEREBRAL EDEMA (part 1) - A. A. Zadvornov; A. V. Golomidov; E. V. Grigoriev (Вестник анестезиологии и реаниматологии)
The brain tissue manifests high metabolic activity and its damage results in disorders in oxygen and nutrients supply, accompanied by a severe life-threatening condition, i.e. cerebral edema. There are several stages of cerebral edema and each stage has unique pathogenic mechanisms. At the stage of cytotoxic edema, the fluid is redistributed into intracellular compartment. Ionic edema is characterized by functional disorder of blood-brain barrier with redistribution of fluid into interstitium. Stages of vasogenic edema and hemorrhagic conversion are manifested through anatomic lesions of blood-brain barrier. Traditional management of cerebral edema such as use of diuretic agents, hyperosmolar solutions, hyperventilation, decompressive craniotomy proved to be ineffective. Current data on pathophysiology of cerebral edema can promote discovering new promising treatment methods.